1995
DOI: 10.1038/ki.1995.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endothelin on hemodynamics, prostaglandins, blood coagulation and renal function

Abstract: The interaction of the endogenous vasoconstrictors endothelin (ET), angiotensin II (Ang II) and catecholamines with the kallikrein-kinin-, prostaglandin and renin-aldosterone systems in the pathogenesis of acute renal failure (ARF) is still to be defined. In 18 anesthesized pigs the influence of i.v. bolus applications of ET (2 micrograms/kg), Ang II (10 micrograms/kg) and norepinephrine (NE; 20 micrograms/kg) on hemodynamics, plasmatic coagulation and fibrinolysis system, prostaglandins and renal function was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…Apart being a potent vasoconstrictor, ET-1 also exhibits hypertrophic, mitogenic and anti-apoptotic effects on vascular smooth muscle cells [50][51][52]. EТ-1 induces strong and prolonged contractile responses in vascular smooth muscle cells in different systems, with a special effect on the renal vascular bed [48,[53][54][55][56]. Initially described as a vasoconstrictor, ET-1 is now acknowledged to participate in the pathogenesis of a number of disorders, i.e.…”
Section: Endothelinmentioning
confidence: 99%
“…Apart being a potent vasoconstrictor, ET-1 also exhibits hypertrophic, mitogenic and anti-apoptotic effects on vascular smooth muscle cells [50][51][52]. EТ-1 induces strong and prolonged contractile responses in vascular smooth muscle cells in different systems, with a special effect on the renal vascular bed [48,[53][54][55][56]. Initially described as a vasoconstrictor, ET-1 is now acknowledged to participate in the pathogenesis of a number of disorders, i.e.…”
Section: Endothelinmentioning
confidence: 99%
“…Moreover, it was shown that the i.v. administration of ET causes a dose-dependent alteration in renal function that has close similarities to that of CsA administration (i.e., increased RVR with subsequent decreased RBF and GFR), suggesting that ET could mediate this phenomenon [6,7,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…administration of ET was shown to cause a dose-dependent and long-lasting decrease in RBF, GFR and urine volume as a result of increased RVR, mesangial cell contraction and decreases in the ultrafiltration coefficient [6,7,8,9]. The decrease in RBF involves vascular contraction of both cortex and medulla with vasoconstriction involving preand postglomerular arterioles as well as the arcuate and interlobular arteries [8].…”
Section: Introductionmentioning
confidence: 98%
“…In a study of acute renal failure in pigs, the administration of ET-1 suggested that ET-1 caused renal dysfunction by severely reducing renal blood flow and the glomerular filtration rate [14]. In patients with chronic renal failure, including those undergoing hemodialysis or continuous ambulatory peritoneal dialysis, ET-1 is elevated in comparison with normal volunteers [15].…”
Section: Discussionmentioning
confidence: 99%